PAPER NAUTILUSES FROM TOMINI BAY PARIGI MOUTONG REGENCY CENTRAL SULAWESI, INDONESIA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Paper nautiluses are classified as Cephalopoda class, Argonautidae family. The aims of this research to identification of shell morphological characters of paper Nautiluses were collected at 1,000 m depth. The results showed that out of all the samples successfully collected during the course of the study (March till December 2016), only 6 specimens were found at 70-80 depth, with 4 of those species are egg-laying, and the other 2 are not. From the 6 species found, 2 were Argonauta argo with average shell length of 34.05 mm, shell width of 22.20 mm, and average aperture width of 11.15 mm. A. argo is known to possess 8 tentacles, 4 long and 2 short appendages. The shell color is brighter than that of A. hians, with flatter shell and two strips of keels located near each other along the dorsal and soft side, along ventral side thickens and sharpens. A. hians possess average shell length of 47.02 mm, shell width of 33.07 mm and aperture width of 21.30 mm. This species has more pronounced and blunt keels along its wide dorsal side, along lateral side the aperture widens and does not have a wing-like form. The riblines found in lateral sides are thicker and moreloose. It is concluded that 2 paper nautilus species were found in Tomini bay, Central Sulawesi, namely A. argo and A. hians.